1992
DOI: 10.1002/art.1780350611
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of circulating intercellular adhesion molecule 1 in kawasaki disease

Abstract: Objective. We investigated whether levels of intercellular adhesion molecule 1 (ICAM-1) antigen shed into the circulation increase during acute Kawasaki disease (KD). We also compared ICAM-1 levels in acute KD with those in anaphylactoid purpura (AP) and in measles.Methods. Serum ICAM-1 levels were measured by a double-determinant immunoassay using 2 monoclonal antibodies in the FAST (Falcon assay screening test) system. Serum levels of tumor necrosis factor a (TNFa) were measured by a specific and sensitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
65
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(77 citation statements)
references
References 26 publications
10
65
0
2
Order By: Relevance
“…In addition, we demonstrated that IgG-APS increased concentrations of sICAM-1, but pretreatment with fluvastatin suppressed this increase. Previous studies have demonstrated that increases in the circulating concentrations of these molecules are proportional to the increases in their cell membrane expression (59)(60)(61)(62)(63). Furthermore, the soluble phase of this molecule seems to have biologic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we demonstrated that IgG-APS increased concentrations of sICAM-1, but pretreatment with fluvastatin suppressed this increase. Previous studies have demonstrated that increases in the circulating concentrations of these molecules are proportional to the increases in their cell membrane expression (59)(60)(61)(62)(63). Furthermore, the soluble phase of this molecule seems to have biologic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular ICAM-1 expression and shedding of ICAM-1 are inducible or augmentable by proinflammatory cytokines (IFN-, TNF-and IL-1 ) [13,14,21]. Elevated concentrations of circulating sICAM-1 have been found in inflammatory diseases such as idiopathic pulmonary fibrosis (IPF) [15], Kawasaki disease [16], rheumatoid arthritis (RA) [17], tuberculosis [18], chronic liver diseases [19] and extrinsic allergic alveolitis [20]. Circulating sICAM-1 concentrations significantly correlate with circulating TNF-concentrations in Kawasaki disease [16], RA [17] and tuberculosis [18], and with circulating IFN-concentrations in tuberculosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Shedding of ICAM-1 is increased by treatment with TNF-and IL-1 [14]. Circulating sICAM-1 has been reported to be elevated in patients with inflammatory diseases [15][16][17][18][19][20], and excess release of proinflammatory cytokines seems to be related to the elevation of circulating sICAM-1 in these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a sustained increase in sICAM-1 was observed even after clinical improvement in other inflammatory diseases [37,38]. Although sICAM-1 levels were still higher after 3 months of steroid therapy, changes in sICAM-1 levels seem to be correlated with the degree of inflammatory activity in GO and the response to steroid therapy, although no direct relation was found between sICAM-1 and the ophthalmopathy-index score.…”
Section: Discussionmentioning
confidence: 90%